The relationship between anxiety and internet gaming disorder in children during COVID-19 lockdown: a network analysis - Yang, Tianqi; He, Yang; He, Chunyan; Yang, Yueqi; Wu, Lin; Wei, Bin; Dong, Ruina; Yang, Mengyuan; Pu, Zhaojun; Wang, Saiming; Li, Jing; Xu, Tao; et al. (Frontiers in Psychiatry, 2023)
Background: Internet gaming disorder (IGD) has become a social problem in children. Evidence from previous studies has proven that anxiety is associated with internet game disorder. However, internet gaming disorder was always assessed as a whole based on total scores, and the fine-grained relationship between anxiety and IGD was hidden. Objective: The present study aims to investigate the fine-grained relationship between anxiety and Internet Gaming Disorder in elementary school students during the COVID-19 lockdown, and to identify potential targets for psychological interventions. Methods: During the lockdown caused by the COVID-19 pandemic, 667 children from a primary school in China were investigated by the Spence Children’s Anxiety Scale-Short Version and Internet Gaming Disorder Scale. R4.1.1 software was used to construct a network model, assess bridge centrality, test the robustness of the network and conduct a network comparison test of gender. Results: There were 23 cross-community edges (weight ranged from -0.03 to 0.12), and each node of anxiety was connected to different nodes of IGD. The nodes with the top 80th percentile bridge expected influence were A2 “social phobia” (0.20), A3 “panic disorder” (0.21) and IGD5 “escape” (0.22). The robustness of the network was acceptable, and there was no significant difference in the network structure between sexes. Conclusion: From the perspective of network analysis, the present study explored the correlation pathways between anxiety and IGD in children and identified social phobia and panic disorder as the best targets for intervention to reduce IGD.